UNLOCKING THE DYNAMIC OF STEM EDUCATION IN MALAYSIA: A BIBLIOMETRIC STUDY - Syed Taufiq Akmal Syed Nasiruddin; Ainorkhilah Mahmood; Nur Maizatul Azra Mukhtar; Nur Iwani Nor Izaham; Mahayatun Dayana Johan Ooi; Naser Mahmoud Ahmed (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
A bibliometric analysis was done to unlock the dynamic of STEM education in Malaysia by revealing the performance and science mapping of the published document in the Web of Science Core Collection for all years refined to only Malaysian published documents. The publication trend of STEM education in Malaysia shows a rise and fall between 2019 and 2023 with an overall publication trend and citation decline after reaching its apex in 2018 and 2021 respectively. Among the states in Malaysia, Selangor exhibits the highest total citation and document count with 178 and 33 respectively compared to other states with Universiti Kebangsaan Malaysia highly contributing to the percentage. Other illuminated data include the performance of organisations, authors and finally the percentage of funding. Furthermore, keyword analysis is illustrated through the science mapping highlighting the STEM education in Malaysia revolving around the interests of sustainable development. Limitations of the studies included the dataset received only from the Web of Science database and not from any other source, for example, Scopus or Google Scholar. The value of the articles lies in assessing the Malaysian tertiary research progress and its impact surrounding the topic of STEM Education in Malaysia.